2015
DOI: 10.1155/2015/826743
|View full text |Cite
|
Sign up to set email alerts
|

Size Control of Alloyed Cu‐In‐Zn‐S Nanoflowers

Abstract: Uniform, alloyed Cu-In-Zn-S nanoflowers with sizes of11.5±2.1 nm and31±5 nm composed of aggregated 4.1 nm and 5.6 nm primary crystallites, respectively, were obtained in a one-pot, heat-up reaction between copper, indium, and zinc acetate withtert-dodecanethiol in the presence of trioctylphosphine oxide. Larger aggregates were obtained by dilutingtert-dodecanethiol with oleylamine, which lowered the reactivity of the indium and zinc precursors and led to the formation of copper rich particles. The thermal deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The t-DDT plays a key role in the shape-controlled synthesis of CIS NCs, acting as both a sulfur precursor and a ligand. This reaction component has been used before to synthesize Cu-In-Zn-S nanoflowers [26]; the authors claimed that the decomposition of surface-bound t-DDT was the reason for the aggregation of smaller NCs to form larger scale nanoflowers. They also observed that the use of the less t-DDT led to the formation of larger size Cu-In-Zn-S nanoflowers.…”
Section: Resultsmentioning
confidence: 99%
“…The t-DDT plays a key role in the shape-controlled synthesis of CIS NCs, acting as both a sulfur precursor and a ligand. This reaction component has been used before to synthesize Cu-In-Zn-S nanoflowers [26]; the authors claimed that the decomposition of surface-bound t-DDT was the reason for the aggregation of smaller NCs to form larger scale nanoflowers. They also observed that the use of the less t-DDT led to the formation of larger size Cu-In-Zn-S nanoflowers.…”
Section: Resultsmentioning
confidence: 99%
“…The small lattice mismatch (about 2%) of CuInS 2 with respect to ZnS is beneficial to the ZnS shelling process. On the other hand, the difference of the ionic diameter between Zn 2+ and Cu + is small enough to favor the partial cation exchange . Therefore, the interplay between the ZnS shelling reaction and partial cation exchange is present in the synthesis of multinary Cu‐In‐S‐based NCs, thus making it difficult to distinguish the genuine nanostructures.…”
Section: Introductionmentioning
confidence: 99%